Effect of the birthing position on its evolution from a biomechanical point of view. (March 2021) - Borges, Margarida; Moura, Rita; Oliveira, Dulce; Parente, Marco; Mascarenhas, Teresa; Natal, Renato
Highlights: Numerical simulations of vaginal deliveries assuming two birthing positions The finite element model includes: fetus head; pelvic bones, ligaments and muscles. In flexible sacrum positions, a higher movement and rotation of the coccyx occurs. In non-flexible sacrum positions, a higher widening of the pubic symphysis occurs. The left area of the levator ani muscles are the most solicited muscles. Abstract: Background and objective: During vaginal delivery, several positions can be adopted by the mother to be more comfortable and to help the labor process. The positions chosen are very influenced by factors such as monitoring and intervention during the second stage of labor. However, there is limited evidence to support the most ideal birthing position. This work aims at contributing to a better knowledge associated with the widening of the pubic symphysis and the biomechanics of flexible and non-flexible sacrum positions that can be adopted during the second stage of labor, as well as their resulting pathophysiological consequences. Methods: A validated computational model composed by the pelvic floor muscles attached to the bones, and a fetus head was used to simulate vaginal deliveries. This model was modified to mimic two birthing positions: one that allows the free movement of the coccyx as in flexible sacrum positions and other in which this movement is more restricted as in non-flexible sacrum positions. The widening of the pubic symphysis was also considered to facilitate the passage of the fetus head. Results: The results obtained showed that, in non-flexible sacrum positions, where the coccyx movement is restricted, occur a rotation of 3.6° of the coccyx and a widening of 6 mm of the pubic symphysis. In contrast, in flexible sacrum positions, where the coccyx is free to move, occur a rotation of 15.7° of the coccyx and a widening of the pubic symphysis of 3 mm, appearing to be more beneficial for the mother's pelvis, but slightly higher stresses were detected in the pelvic floor muscles. Conclusions: Globally, the results obtained allow to conclude that different birthing positions lead to changes in the female pelvic space, so certain positions can be adopted by the mother during the second stage of labor to reduce the risk of obstructed labor and the development of several dysfunctions. More specifically, flexible sacrum positions, such as kneeling, standing, squatting and sitting positions, are more beneficial for the bone structure of her pelvis as they allow a higher coccyx movement and lower widening of the pubic symphysis.